Contributions to the knowledge of Euschistus (Lycipta) with the description of E. (L.) riograndensis sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) - Weiler, Luciana; Ferrari, Augusto; Grazia, Jocelia (Zootaxa, 2011)
Lycipta Stål (1862a) was proposed as a genus to include three species previously placed in Euschistus Dallas – Euschistus illotus Stål, 1860; E. triangulator (Herrich-Schäffer, 1842); and E. scabricornis (Herrich-Schäffer, 1844). Later, Stål (1862b) treated Lycipta as a subgenus of Euschistus and described E. (L.) spurculus. Stål (1872) transferred E. spurculus to Euschistus (Euschistus); treated E. scabricornis as inserti generis (actually Agroecus scabricornis); and added three new species to Euschistus (Lycipta). As a result (Stål 1872), there are five species: E. (L.) cornutus (Dallas, 1851); E. (L.) cribrarius Stål, 1872; E. (L.) illotus; E. (L.) picticornis Stål, 1872; and E. (L.) triangulator. Rolston (1982) added five new species to Lycipta: E. (L.) luridus (Dallas, 1851); E. (L.) circumfusus Berg, 1883; E. (L.) imitator Berg, 1878; E. (L.) machadus Rolston, 1982; and E. (L.) sharpi Bergroth, 1891. Thomas (1983) corrected the homonymy of Euschistus luridus Dallas, 1851, replacing the name of E. (L.) aceratos Berg, 1894. Grazia & Hildebrand (1982) transferred Berecynthus monrosi Pirán, 1963 to Euschistus; Rolston (1984), based on the illustrations of the head and spermatheca of E. monrosi provided by Grazia & Hildebrand (1982), included this species in the subgenus Lycipta. Finally, Grazia & Hildebrand (1983) described E. (Lycipta) longicornis, for a total of 12 species in the subgenus.